Career Guidance Media in Vocational High Schools: A Literature Review of Its Role in Enhancing Students' Career Readiness - Puspitasari, Desty Ratih; Ariani, Dian; Pangestu, Divan Robi; Purwanto, Dwi; Amaliyah, Fitri (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This study is a narrative literature review aiming to identify and summarize various research findings related to media use in career guidance services at Vocational High Schools (SMK). By examining 41 scholarly articles published over the past ten years, this study presents key themes that have captured researchers' attention, including: the need for and development of career guidance media, the effectiveness of digital media in supporting career planning, the impact of guidance services on students' career readiness, student-centered guidance approaches, and the alignment of career programs with labor market demands. The findings reveal that career guidance media are not merely supplementary tools but essential strategies to bridge students with the ever-changing demands of the workforce. Technological advancements have stimulated innovation in career guidance services, such as digital applications, interactive media, e-modules, online counseling management systems, and approaches based on multiple intelligences and interest-talent profiling, proving effective in facilitating exploration and decision-making. Furthermore, collaboration among school counselors, students, and industry stakeholders is crucial for successful career services. This study recommends that career guidance in vocational schools be adaptive, technology-integrated, and aligned with 21st-century competencies to enhance graduates' employability.